Leveraging AI Chatbots in ESP: The Role of Digital Readiness in Enhancing Vocational Students’ Willingness to Communicate - Nurul Inayah Hutasuhut; Weria Hendri; Ahmad Fadli Harahap (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This research investigates the effects of digital readiness and using AI chatbots affects vocational students’ willingness to communicate in English, specifically for work or study purposes. The study used a questionnaire to collect data from 182 students in Sumatera, Indonesia and then analyzed the results to see how digital readiness and chatbot use individually and together impact students’ willingness to communicate in English. The findings reveal that both digital readiness and AI chatbot use significantly and positively influence students’ WTC, with digital readiness emerging as the stronger predictor. The model explains a substantial proportion of variance in WTC, indicating that students’ preparedness to engage with digital technologies plays a critical role in maximizing the benefits of AI-mediated learning environments. AI chatbots were found to enhance communicative confidence, reduce anxiety, and encourage active participation in English communication. A novel contribution of this study is the identification of the dual role of learners’ mother language (L1). While strategic L1 use supports idea formulation and boosts confidence, excessive reliance may hinder spontaneous communication. AI chatbot interaction appears to facilitate a gradual shift from L1 dependence to more autonomous L2 use. These findings offer important theoretical and pedagogical implications for technology-enhanced ESP learning in vocational education contexts.